2018
DOI: 10.1177/2054358117753619
|View full text |Cite
|
Sign up to set email alerts
|

Nephrology eConsults for Primary Care Providers: Original Investigation

Abstract: Background:The Champlain BASE™ (Building Access to Specialists through eConsultation) eConsult service allows primary care providers (PCPs) to submit patient-specific clinical questions to specialists via a secure web service.Objective:Our objective was to describe the types of nephrology questions asked through an eConsult service based in eastern Ontario and assess the service’s impact on the need for face-to-face consultations.Design:Cross-sectional study using descriptive statistics was conducted using nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
(21 reference statements)
2
23
0
Order By: Relevance
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
See 1 more Smart Citation
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
“…62 Several publications from the Champlain BASE program report on a PCP survey question at the end of each e-consult request about whether a face-to-face consult would have been sent in the absence of the e-consult option. Depending on specialty of the consultation being requested, 32%-80% of PCPs report that a face-to-face visit would have been required absent the e-consult, [12][13][14]16,[18][19][20][21]24,26,[28][29][30][31][32][33][34][35][36]41,47,51,58,62,65 suggesting that up to as many as 4 out of 5 e-consults are perceived to obviate a face-to-face visit. Using these data on face-to-face referrals avoided, the Champlain BASE group calculated payer costs decreasing from $131.05 to $6.45 (CAD) per econsult from year 1 to year 3 of the program.…”
Section: Costsmentioning
confidence: 99%
“…This approach has been increasingly adopted by health care systems and has been shown to improve the timeliness and efficiency of specialty care. 26,[30][31][32] In the US Veterans Health Administration, e-consults are heavily utilized and its success is largely due to its integration within the existing EMR which made it convenient and easy for providers to use. Also, each specialty had the flexibility to determine how it would triage and assign responsibility for submitted e-consults.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in an increased use of telehealth, which allows clinicians to interact with patients from remote sites. 34-36…”
Section: Discussionmentioning
confidence: 99%